UJI VIABILITAS TERHADAP BENIH POLYEMBRIONI - Jasmi Jasmi (Universitas Teuku Umar, 2020)
Seeds are mature ovules. One or more of the ovaries formed in the legume, but never more than one seed formed in the ovaries of monocots. Each ripe seed always consists of at least two parts, namely: (1) Embryo, (2) Seed coat (Seed coat or testa). Embryo is formed or derived from fertilized eggs (zygote) by undergoing cell division in the embryo sac. Seed coat is formed from the integument (one or more) of the ovules. In legumes generally there are two layers of seed coat. Every very young and growing seed always consists of three parts: (1) Embryo, (2) seed coat, (3) Endosperm. Endosperm is a storage food storage network which is absorbed by the embryo before or during seed germination and is always present in very young seeds. Polyembryonics is the presence of more than one embryo in one seed, but these embryos do not always mature or mature, remain undeveloped or degenerate. The purpose ofthis research is to study the germination of one seed that has more than one embryo and to determine the growth of seedlings from polyembryonic seeds. The results showed that the highest plant growth (plant height, number of leaves, fresh weight and dry weight of orange seeds) was found in orange seeds that had 1 embryo compared to orange seeds which had 2 and 3 embryos. Seed germination and growth is strongly influenced by the amount of food reserves stored in seeds (Magagula and Ossom 2011 in Hasnah M, 2013).